Strengthening the Capacity of Village Communities in Handling Health Crises Due to Disasters Through Participatory Action Research: Results of Community Service in Ngelang [Accepted] - Sunarto Sunarto; Heru Santoso Wahito Nugroho; Suparji Suparji; Aries Prasetyo; Cantika Puteri Apriliana (Health Dynamics, 2026)
Ngelang Village in Kartoharjo District, Magetan Regency, has been designated a Disaster Resilient Village (Destana). However, its capacity to handle health crises remains limited, marked by weak coordination, the absence of an emergency command structure, and minimal training and simulation. The community service activity employed a Participatory Action Research (PAR) approach and involved 34 participants. Needs identification resulted in four priorities: establishing a command structure, developing a contingency plan, updating health vulnerability data, and creating a risk and vulnerability map. Intensive training was conducted over four days, totaling 30 training hours (JPL). The average pre-test score of 77.07 increased to 86.4 in the post-test, but decreased to 81.03 after one month, indicating challenges in knowledge retention. Participation was high, with over 59% of responses in the excellent category. Weaknesses were still evident in discussion engagement and problem-identification skills. Reflection showed that material understanding and practical skills were in the moderate category, while engagement was relatively high. The PAR intervention was effective in increasing knowledge and participation; however, the sustainability of the results requires strengthening retention strategies. Active participant involvement is crucial, but improvements are needed in discussion and problem analysis. The village government is committed to allocating the village budget (APBDes) for evacuation facilities, outreach, and regular simulations. The Destana Forum has agreed to make the training a regular biennial program and establish collaborations with health and disaster management agencies.